MENTORING SECOND SEMESTER UNIVERSITY STUDENTS’ READING SKILLS AT UNIVERSITAS ISLAM TRIBAKTI LIRBOYO KEDIRI AND UNIVERSITAS NUSANTARA PGRI KEDIRI THROUGH EXTENSIVE READING - Ummy Khoirunisya' Masyhudianti; Khoiriyah; Ei Mon Kyaw; Mochammad Abdullah Salim; Rahayu Meliasari; Muhammad Raihan (BHAKTI: JURNAL PENGABDIAN DAN PEMBERDAYAAN MASYARAKAT, 2025)
This community service project aimed to enhance the reading skills of second-semester university students at Universitas Islam Tribakti Lirboyo Kediri and Universitas Nusantara PGRI Kediri through an extensive reading program. The program, conducted from April to July 2025, involved 59 students and included training sessions and seminars focused on extensive reading strategies. The objective was to improve students' vocabulary, reading comprehension, and overall reading interest. This study employed a service-learning approach that included four key stages: investigation, preparation, action, and reflection. During the investigation stage, a pre-test and observations were conducted to assess students' baseline reading abilities. The results of the program showed significant improvements in students' vocabulary, reading comprehension, and reading interest. The program not only helped students understand academic texts more effectively but also fostered a more positive attitude toward reading. These findings suggest that extensive reading can significantly contribute to the development of essential literacy skills in EFL students. The program's success highlights the potential of using extensive reading as a key strategy to enhance students' language proficiency and foster a lifelong reading habit.